Optimization of Waste Cooking Oil’s FFA as Biodiesel Feedstock - Primandari, Sri Rizki Putri; Arafat, Andril; Veny, Harumi (Universitas Negeri Padang, 2021)
Waste cooking oil has high Free Fatty Acid (FFA). It affected on decreasing a biodiesel production. FFA reduction is one of important processes in biodiesel production from waste cooking oil. Thus, this study aimed to examine the optimum condition in FFA reduction. The process is assisted by using ultrasonic irradiation on acid esterification. Variables of the process are acid concentration, molar ratio of methanol and oil, and irradiation time. Meanwhile temperature irradiation on 45oC is a control variable. Process optimization is conducted by Response Surface Methodology (RSM) with Central Composite Design (CCD). The optimum conditions of response were 7.22:1 (methanol to oil molar ratio), 0.92% wt H2SO4, 26.04 minutes (irradiation time), and 45oC (irradiation temperature). Ultrasonic system reduced FFA significantly compared to conventional method.